Survey of hydrocarbon deposits based on the analysis of space and surface information via methods of multi-criteria optimization and analytical networks (case of the Dnieper-Donets depression) - Khyzhnyak, A.V.; Arkhipov, O.I.; Fedorovsky, O.D.; Yephimenko, T.A. (Reports of the National Academy of Sciences of Ukraine, 2017)
As exemplified by the case of the Turutynsko-Rohintsivskaya zone in the Dnieper-Donets depression, the potential for the assessment of onshore oil and gas prospects is substantiated on the basis of the analysis of space and surface information through methods of multi-criteria optimization and analytical networks.